Principles of shaping in organic design in context development of modern architecture - Papeta, Olena; Zghalat-Lozynska, Natalia (Theory and practice of design, 2022)
Notice: The authors sincerely apologize for the citation mistake in the article "Principles of shaping in organic design in context development of modern architecture", namely, a lack of reference to Olena Pavlivna Oliynyk’s article. Relevant corrections have been made to the text on page 159 and the reference list. The aim of the article is to highlight the basic principles of formation in organic design and architecture at the present stage of development based on the study of existing buildings, design objects and innovative projects related to organic architecture, as well as analysis of historical background of organic design. Methodology. The main goal of present work is the analysis of constructivism and functionalism elements, as well as formal techniques peculiar to modern developments in this field of construction, in the context of modern research in organic architecture. The problem of synthesis plastic and color solution in the design considers in the current research. Results. The examples of modern buildings related to organic architecture and features of their formation were observed. The basic principles of organic design, on which designers and architects rely in the process of creating a project, are also formulated. The problem of shaping organic design objects has been investigated at the present study. Scientific novelty. The article’s novelty is the theoretical generalization of the principles of shaping in organic design, based on the considered design and multifaceted study of historical origins of style, varieties and techniques used to design products, and an example of applying this information in practice as an element. era for public institutions. Practical significance. This architectural style is in the process of active development, as a result of which the study of the principles of formation in organic architecture and design is an extremely relevant topic that needs the theoretical generalization for its further implementation in urban planning practice.